Spectral-Domain Optical Coherence Tomography for Macular Edema - Badaro, Emmerson [UNIFESP] (2014)
Optical coherence tomography (OCT) is a rapid noncontact method that allows in vivo imaging of the retina and it has become an important component in clinical practice. OCT is a useful ancillary tool for assessing retinal diseases because of its ability to provide cross-sectional retinal images and quantitatively analyze retinal morphology. the introduction of spectral-domain OCT provided major improvements in image acquisition speed and image resolution. Future studies will address how these major technologic advances will impact the use of OCT in research and clinical practice.